Expressive Illocutionary Act in the Little Mermaid 1989 Movie - Trisnawati, Ni Kadek Dian; Eka Pratiwi, Desak Putu; Andri Permana, I Putu (e-Journal of Linguistics, 2022)
This article discusses about expressive illocutionary act in The Little Mermaid 1989 Movie. This article analyzing the data used descriptive qualitative method. The aims of this article are to identify the types of expressive illocutionary act and the context of situation in the movie. This article used theory by Searle (1979) to identify the types of expressive illocutionary act and theory by Halliday and Hasan (1985) to analyze the context of situation. The result of this article showed 22 utterances which are produced by the characters.